Hubungan Penggunaan Media Pembelajaran dengan Minat Belajar Matematika Siswa Kelas IV SD - Musdalifah, Musdalifah; adnan K, adnan K; Latri, Latri; Djafar, Muh. Idris (Universtas Negeri Makassar, 2022)
This research is a correlational quantitative research that aims to determine the relationship between the use of instructional media and the interest in learning mathematics for fourth graders of SD Gugus II, Kecamatan Sibulue, Kabupaten Bone. The data in this study were collected by questionnaire and processed using descriptive statistical analysis and inferential analysis. The results showed that there was a significant relationship between the use of instructional media and the interest in learning mathematics for fourth graders of SD Cluster II with rcount (0.584) greater than rtable (0.212), which means H0 is rejected and H1 is accepted. Based on the results of the study, it can be concluded that the use of learning media in the teaching and learning process has an impact on student responses so that it will affect students' interest in learning, especially mathematics. So, the better the use of learning media it will increase student interest in learning. The impact of this research is that the use of learning media that is carried out appropriately according to the characteristics of the media, needs, and learning objectives can increase interest in learning mathematics so that students will obtain good learning outcomes and achieve learning success.